A CASE tool for modelling and automatically generating web service-enabled applications. (21st July 2006) - Brambilla, Marco; Ceri, Stefano; Comai, Sara; Fraternali, Piero
This paper presents a CASE tool for the high-level specification of web applications integrated with web services. The CASE tool is based on WebML, a conceptual modelling language used for the specification of the front end of web applications. WebML, extended with new primitives for modelling web services, allows one to specify complex interactions between a web application, driven by the user, and remote processes, represented by services. The CASE tool also allows the specification and deployment of application functionalities as web services and automatically generates the running code, including web pages, web services calls and the exposed web services. In this paper, we describe the primitives for web services modelling, the architecture of the CASE tool for designing the applications, and the runtime architecture of the generated applications. Finally, we give an overview of some industrial applications developed with the described approach.